Direct dan Indirect Effect: Determinan Upah Minimum Kabupaten/Kota di Jawa Barat - Husada, Alphin Pratama; Yuhan, Risni Julaeni (Jurnal Ekonomi dan Pembangunan Indonesia, 2022)
This study aims to analyze the determinants of the regional minimum wage (UMK) directly and indirectly in West Java in year 2010–2019. The author found that the minimum wage model that considers spatial dependence produces two different interpretations, namely direct and indirect impacts. The regression model used in this study is the spatial durbin model (SDM). In the spatial model, partial reduction is carried out to get direct and indirect effects. The results of the study show that there are direct and indirect influences originating from the MSE variables, Gross Regional Domestic Product (GRDP), Human Development Index (HDI) and the Labor Force Participation Rate (TPAK).